A multimodal approach of sentiment analysis to predict customer emotions towards a product - Islam, Shadman; Rahman, Moshiur; Ali, Samina Tuz Zohura; Shahrior, Tawhid (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.